Does Gender Difference Impact Investment Decisions? Evidence from Oman - Jamil, Syed Ahsan; Khan, Khaliquzzaman (International Journal of Economics and Financial Issues, 2016)
Humans are believed to be rational decision makers and documentary evidence proves a significant heterogeneity across individuals when it comes to investment decision making and risk bearing. The study is an attempt to explore and understand the heterogeneity of investment decision when it comes to gender behavior with focus on women. The aim of this research is to explore role of gender in investment decision making and to identify the points of difference between the two genders with respect to their vulnerability towards various behavioral bias in their pursuit for prospective financial gains. The research attempts to understand the susceptibility of genders to normative influences and herd tendencies in the context of Oman. Keywords: Behavioral finance, prospect theory, risk, herd behavior JEL Classifications: G02, G21, G24